Multi-scale foraging decisions made by woodland caribou (Rangifer tarandus caribou) in summer - McNeill, Eric (University of Guelph, 2015)
Multi-scale selection patterns can be understood from two perspectives: one that sees coarse scale patterns as the summation of fine scale patterns and the other that sees it as a hierarchy produced from multiple contributory factors. Here I examine caribou selection of foraging locations across three spatiotemporal scales to determine if caribou foraging behavior is hierarchical or scaling-up in nature. Seven adult female caribou were equipped with GPS telemetry radio-collars with high definition video cameras that recorded foraging choices throughout the summer. Fine-scale data from videos were used to estimate food plant selection across feeding stations, food patches, and forest stands. Caribou exhibited resource selection at all spatial scales, with some patterns consistent across some scales. The resource use patterns suggested selection at one or two scales, but not at all scales. My study suggests that even at very fine scales, caribou selection for foraging locations is hierarchical.